Perception and Capacity of People with Disabilities Entering the Malaysia Construction Industry: Preliminary Findings - Masidah, Abdul Majid; Nurul Aini, Osman; Mohd Saifulnizam, Mohd Suhaimi; Suhaida Suhana, Kamarudin; Norul Izzati, M. Ashaari (IOP Publishing, 2023)
People with Disabilities (PWDs) seek the same chances and experiences as everyone else, yet due to a number of hurdles they are frequently excluded from fulfilling jobs. There are few statistics available globally to give an accurate knowledge of the number of workers with disabilities, and there is still a dearth of study on employment, disability, and construction, particularly in Malaysia. This study aims to determine the students and trainer at the Industrial Training and Rehabilitation Centre for People with Disabilities (PLPP) in Bangi, Selangor feel about participating the construction industry and their capacity to do so. It investigates how eager and capable students are to meet the requirements of IR4.0 in the construction industry. The interviews with 2 students who have physical disabilities, and 1 instructor are included in the data. These students are registered and classified as physical disability by the Malaysian Social Welfare Department. The interviews were transcribed verbatim. Extracting, grouping, and interpreting keywords or phrases into themes. The results show the PWDs have a high motivation to have an added-on skill in IR4.0 courses like drone, BIM and VR which will open bigger opportunity to enter construction industry. It also reveals that the participants have a basic skill of AutoCAD which shows that they able to perform a technical understanding.